Malunions and nonunions following tibial malleolar and tibial plafond fractures: current concepts - Vicenti, Giovanni; Bizzocca, Davide; Scialpi, Lorenzo; De Carolis, Oronzo; Carrozzo, Massimiliano; Moretti, Biagio (Lo Scalpello - Journal, 2020)
Ankle fractures or fracture-dislocations account for about 4-5% of all body fractures, with approximately 120-180/100,000 affected persons/year. Tibial pilon fractures are relatively infrequent, accounting for 5–7% of all fractures of the tibia. This review aims to summarize the current evidence on malunions and nonunions following tibial malleolar and tibial plafond fractures and to give some tips to avoid such complications. Malunion and nonunion following tibial malleolar and plafond fractures are quite rare but dreadful complications. Accurate evaluation of comorbidities and optimization of the patient’s health should be done before surgery. Multiple recent retrospective studies have shown that ankle/ tibial plafond fractures treated within 72 h of surgery have comparable outcomes to staged fixation, the two-stage protocol is the most commonly used approach for the treatment of high-energy intra-articular injuries of the distal tibia. Several surgical approaches have been described for the management of ankle and tibial plafond fractures. Each one of these approaches has its own advantages and disadvantages, hence, it is important to recognize that no one approach is right for all patients. Surgeons managing these complex fractures should be comfortable with the various approaches to the distal tibia and be prepared to use whichever approach is suitable for the individual soft tissues and fracture pattern. Finally, with improvements in surgical techniques and implants, complication rates following ankle and tibial plafond fractures have declined, and outcomes have improved.